Role of Autophagy in Cancer Prevention - Chen, Hsin-Yi; White, Eileen (Cancer prevention research (Philadelphia, Pa.), 2011)
Macroautophagy (autophagy hereafter) is a catabolic process by which cells degrade intracellular components in lysosomes. This cellular garbage disposal and intracellular recycling system maintains cellular homeostasis by eliminating superfluous or damaged proteins and organelles and invading microbes and by providing substrates for energy generation and biosynthesis in stress. Autophagy thus promotes the health of cells and animals and is critical for the development, differentiation, and maintenance of cell function and for the host defense against pathogens. Deregulation of autophagy is linked to susceptibility to various disorders including degenerative diseases, metabolic syndrome, aging, infectious diseases, and cancer. Autophagic activity emerges as a critical factor in the development and progression of diseases that are associated with increased cancer risk as well as in different stages of cancer. Given that cancer is a complex process and autophagy exerts its effects in multiple ways, the role of autophagy in tumorigenesis is context-dependent. As a cytoprotective survival pathway, autophagy prevents chronic tissue damage that can lead to cancer initiation and progression. In this setting, stimulation or restoration of autophagy may prevent cancer. In contrast, once cancer occurs, many cancer cells upregulate basal autophagy and utilize autophagy to enhance fitness and survive in the hostile tumor microenvironment. These findings revealed the concept that aggressive cancers can be addicted to autophagy for survival. In this setting, autophagy inhibition is a therapeutic strategy for established cancers. Cancer Prev Res; 4(7); 973–83. ©2011 AACR.